2017
DOI: 10.33899/ijvs.2017.145567
|View full text |Cite
|
Sign up to set email alerts
|

Pathological study of subchronic oral toxicity induced by Di (2- ethyl hexyl) phthalate in Japanese quails

Abstract: In present study, we aimed to investigate the pathological changes induced by subchronic oral toxicity induced by sub lethal dose of Di (2-ethyl hexyl) phthalate (DEHP) in Japanese common quail. Forty male quails at one day old were divided randomly into two equal groups, the first group (treated group) was orally administrated by 10% of LD 50 of DEHP (557.41 mg/kg of body weight) for 42 days, while second group (control group) left without treatment throughout experiment period. The results of current study s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Depending on previous scientific studies, the oral LD50 of DEHP during 24 hours was estimated at 5574.1 mg/kg of quail's body weight (6,7). The current study used 5% of LD50 of DEHP, which is estimated by 278.05 mg/kg bw, the dose volume is 0.3 milliliters/quail by oral gavage needle (7).…”
Section: Dehp Dose and Administrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on previous scientific studies, the oral LD50 of DEHP during 24 hours was estimated at 5574.1 mg/kg of quail's body weight (6,7). The current study used 5% of LD50 of DEHP, which is estimated by 278.05 mg/kg bw, the dose volume is 0.3 milliliters/quail by oral gavage needle (7).…”
Section: Dehp Dose and Administrationmentioning
confidence: 99%
“…DEHP is widely used in the poultry industry as an additive to water and feeding supplies, also used in cages of layer hens, drugs and vaccine plastic containers, as a preservative to feed additives, wooden litter to prevent worm infestation, and in the main tanker for water supplies that made from poly vinyl chloride (PVC) (5). Many previous studies have been conducted on the toxicity of DEHP in different types of aviary species, included quails, one of these studies estimated the median lethal dose (LD50) by 5574.1 mg/kg of body weight (6), another study showed that the liver and kidney consider the main sites were the pathological lesions have been recorded (7). DEHP has a unique chemical reaction with materials added to them; it does not react with other molecules' chemical bonds, but it covers other materials' molecular composition.…”
Section: Introductionmentioning
confidence: 99%
“…In commercial poultry farms [7]. Understanding the epidemiology of M. gallisepticum infection is critical for implementing effective control measures and reducing the disease's impact on poultry production [8].…”
Section: Introductionmentioning
confidence: 99%
“…During the 19 th -century, molecular pathology immunohistochemistry and electron microscopy were created and widely applied on scientific bases; these new techniques and protocols helped scientists to study diseases at the cellular and molecular levels (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%